Transverse Anisotropy and Dimensional Stability of Thermal Treated Beech Red Heartwood - Nikola Mihajlovski; Konstantin Bahchevandjiev (TEM Journal, 2017)
This research is mainly focused on the impact of thermal modification on the transverse anisotropy and dimensional stability of native beech wood (Fagus sylvatica L.) and beech red heartwood. Applied to two time-temperature regimes, the first period of maximum temperature to 180° C and the second to 230° C. The factor of anisotropy in native beech wood is 1.29 and beech red heartwood is 1:24. Dimensional stability of the native beech wood is improved for 33.3% and beech red heartwood for 29.1%. The changing of the volume mass per thermal modification of 6% is too small and does not affect other properties.
Keywords: native beech wood, beech red heartwood, thermal modification, dimensional stability.